Crystal form modifier for phosphating film and preparation method thereof
Patent Information
- Application Number
- CN202611038466.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-13
- Publication Date
- 2026-10-16
AI Technical Summary
本发明专利通过引入特定结构的稀土络合物作为环保型促进与晶型调控核心,实现了磷化过程的高效催化与晶粒超细化,并避免了有毒金属离子的使用;通过复配纳米晶核诱导剂,为磷化结晶提供了大量外来的、高度分散的异相成核点位,与稀土离子的催化作用协同,进一步确保了磷化膜晶粒的细密与均匀;通过主成膜剂与有机酸络合剂的配伍,以及pH缓冲剂的调节,实现了对磷化液体系中金属离子浓度的稳定控制与磷化结晶相组成的主动引导;通过氧化剂与表面活性剂的协同,优化了磷化反应界面的微环境,确保了改进剂功效的充分发挥和磷化膜的整体质量;通过独特的“分步溶解、低温混合、顺序添加、充分熟化”的制备方法,确保了各功能组分特别是纳米材料的高度、稳定分散,以及各组分间的相容性与协同稳定性。
Abstract
Description
Technical Field
[0001] This invention patent relates to the field of modifier technology, specifically to a crystal form modifier for phosphating films and its preparation method. Background Technology
[0002] Phosphating is a pretreatment technology widely used in coating, rust prevention, and wear resistance of metallic materials (especially steel, zinc, and their alloys). Its principle is to generate a porous crystalline film, mainly composed of insoluble phosphates, on the metal surface through chemical and electrochemical reactions. The main functions of this phosphate film include: improving the corrosion resistance of the substrate; enhancing the adhesion of subsequent organic coatings (such as paints and powder coatings); and providing certain lubrication and friction-reducing properties.
[0003] The performance of phosphating films, especially their corrosion resistance and adhesion to coatings, largely depends on the crystal morphology of the phosphating film, including grain size, shape, distribution density, and the composition of the crystalline phases. An ideal phosphating film should have fine, uniform, dense grains and low porosity. Currently, zinc-based, zinc-calcium-based, and manganese-based phosphating solutions are commonly used in industry, and film formation and grain refinement are accelerated by adding promoters such as nitrates, nickel ions, and manganese ions.
[0004] However, existing technologies still have some shortcomings: First, while traditional accelerators can refine grain size, they are themselves environmentally toxic, and increasingly stringent environmental regulations restrict their use. Second, the grain size of phosphate films formed by ordinary phosphating treatment is still not uniform enough, easily producing coarse columnar or needle-like crystals, resulting in a non-dense film layer, allowing corrosive media to easily penetrate along the grain boundaries. Third, the bonding strength between the phosphate film and the metal substrate, as well as the stability of its internal crystal structure, needs to be improved; adhesion decreases rapidly in harsh environments. Fourth, existing technologies have limited control over the crystalline phase of the phosphate film, making it difficult to actively induce the formation of specific phosphate crystal forms with superior corrosion resistance.
[0005] In view of this, we propose a crystal form improver for phosphating films and a preparation method thereof.
[0006] Invention Patent Content The purpose of this invention is to provide a crystal form improver for phosphating films and a preparation method thereof, so as to solve the problems existing in the above-mentioned background art.
[0007] To achieve the above objectives, this invention provides the following technical solution: A crystal form improver for phosphating films, comprising the following raw materials in parts by weight: 20-40 parts of main film-forming agent 5-15 parts of rare earth complex, 1-5 parts of nanocrystal nucleation inducer 3-10 parts of organic acid complexing agent 2-8 parts of oxidant Surfactant 0.5-3 parts, 1-5 parts pH buffer 100-200 parts deionized water; The primary film-forming agent is at least one of zinc dihydrogen phosphate, manganese dihydrogen phosphate, and calcium dihydrogen phosphate; the rare earth complex is a water-soluble complex formed by a rare earth element and an organic ligand, wherein the rare earth element is selected from at least one of cerium, lanthanum, and yttrium; and the nanocrystal nucleation inducer is at least one of nano-silica, nano-alumina, and nano-zeolite powder, with an average particle size of 10-100 nanometers.
[0008] Preferably, the organic ligand in the rare earth complex is selected from at least one of citric acid, tartaric acid, gluconic acid, aminotrimethylphosphonic acid, and hydroxyethylidene diphosphonic acid.
[0009] Preferably, the organic acid complexing agent is selected from at least one of citric acid, tartaric acid, oxalic acid, aminotrimethylenephosphonic acid, and sodium ethylenediaminetetramethylenephosphonate.
[0010] Preferably, the oxidant is selected from at least one of sodium nitrate, sodium nitrite, sodium chlorate, hydrogen peroxide, and sodium perborate.
[0011] Preferably, the surfactant is a nonionic surfactant selected from at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and sorbitan fatty acid ester polyoxyethylene ether.
[0012] Preferably, the pH buffer is selected from at least one of boric acid, borax, disodium hydrogen phosphate, and sodium bicarbonate.
[0013] A method for preparing a crystal form modifier for phosphating films includes the following steps: S1. In a reaction vessel, add 60%-80% of the formula amount of deionized water, heat to the first temperature, and add the main film-forming agent and the organic acid complexing agent in sequence while stirring. Continue stirring until completely dissolved to obtain clear solution A. S2. In another container, add the remaining deionized water, add the nanocrystal nucleus inducer while stirring, and process with a high-shear dispersion device to obtain a uniformly dispersed liquid B. S3. Cool the A solution obtained in step S1 to a second temperature, and add the rare earth complex, the oxidant, the surfactant and the pH buffer in sequence while stirring. Ensure that each component is completely dissolved before adding the next one. After all components are added and mixed evenly, slowly add the B solution obtained in step S2 while stirring. After adding all components, continue stirring for a third time, and then let it stand and mature for a fourth time to obtain the crystal form improver of the phosphating film.
[0014] Preferably, in step S1, the first temperature is 50℃-70℃.
[0015] Preferably, in step S3, the second temperature is 30℃-45℃.
[0016] Preferably, in step S3, the third time period is 30-60 minutes, and the fourth time period is 12-48 hours.
[0017] By employing the above technical solution, this invention patent provides a crystal form improver for phosphating films and a method for preparing them. It possesses at least the following beneficial effects: This invention patent achieves highly efficient catalysis and ultrafine crystallization in the phosphating process by introducing rare earth complexes with specific structures as environmentally friendly promoters and crystal form control cores, while avoiding the use of toxic metal ions. By compounding nanocrystal nuclei inducers, a large number of exogenous, highly dispersed heterogeneous nucleation sites are provided for phosphating crystallization, synergistically ensuring the fineness and uniformity of the phosphating film crystals in conjunction with the catalytic effect of rare earth ions. Through the compatibility of the main film-forming agent and organic acid complexing agent, and the adjustment of pH buffers, stable control of the metal ion concentration in the phosphating solution system and active guidance of the phosphating crystallization phase composition are achieved. The synergy of oxidants and surfactants optimizes the microenvironment of the phosphating reaction interface, ensuring the full utilization of the modifier's efficacy and the overall quality of the phosphating film. The unique preparation method of "stepwise dissolution, low-temperature mixing, sequential addition, and thorough maturation" ensures the high and stable dispersion of each functional component, especially the nanomaterials, as well as the compatibility and synergistic stability between the components. Detailed Implementation
[0018] The technical solutions in the embodiments of this patent will be clearly and completely described below with reference to the present invention. Obviously, the described embodiments are only a part of the embodiments of this patent, and not all of them. Based on the embodiments of this patent, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this patent.
[0019] This invention provides a crystal form improver for phosphating films, composed of the following raw materials in parts by weight: 20-40 parts of main film-forming agent 5-15 parts of rare earth complex, 1-5 parts of nanocrystal nucleation inducer 3-10 parts of organic acid complexing agent 2-8 parts oxidant Surfactant 0.5-3 parts, 1-5 parts pH buffer 100-200 parts deionized water; The main film-forming agent is at least one of zinc dihydrogen phosphate, manganese dihydrogen phosphate, and calcium dihydrogen phosphate; the rare earth complex is a water-soluble complex formed by a rare earth element and an organic ligand, wherein the rare earth element is selected from at least one of cerium, lanthanum, and yttrium; and the nanocrystal nucleation inducer is at least one of nano-silica, nano-alumina, and nano-zeolite powder, with an average particle size of 10-100 nanometers. It should be noted that the primary film-forming agents (such as zinc dihydrogen phosphate and calcium dihydrogen phosphate) provide the zinc, calcium, and phosphate ions required to form the phosphate film crystals (such as zinc phosphate and zinc calcium phosphate). Selecting at least two primary film-forming agents in combination, such as the combination of zinc dihydrogen phosphate and calcium dihydrogen phosphate in Example 1, helps to form a more stable zinc calcium phosphate (Hopeite) phase, thereby improving the corrosion resistance of the phosphate film. Rare earth complexes and nanocrystal nucleation inducers are key to achieving ultrafine and uniform grain size. Rare earth elements (such as cerium and lanthanum) can catalyze the reaction and refine the grains, while nanoparticles (such as silicon dioxide with a particle size of 30 nm) act as heterogeneous nucleation sites, increasing the nucleation density.
[0020] The organic ligand in the rare earth complex is selected from at least one of citric acid, tartaric acid, gluconic acid, aminotrimethylphosphonic acid, and hydroxyethylidene diphosphonic acid. It should be noted that the above-mentioned organic acids were chosen as ligands for rare earth elements mainly based on two points: First, these organic acids can form stable water-soluble complexes with rare earth ions, preventing the rare earth ions from precipitating prematurely in the alkaline environment of the phosphating solution, ensuring their stable existence and effectiveness; second, most of these ligands themselves also have complexing effects, which can help stabilize other metal ions (such as Zn²⁺ and Ca²⁺) in the phosphating solution.
[0021] The organic acid complexing agent is selected from at least one of citric acid, tartaric acid, oxalic acid, aminotrimethylenephosphonic acid, and sodium ethylenediaminetetramethylenephosphonate. It should be noted that the main function of organic acid complexing agents is to complex the main metal ions (such as Zn²⁺, Ca²⁺, Mn²⁺) in the phosphating solution. By forming soluble complexes, they act as a "slow-release" agent, preventing excessively high local ion concentrations that could lead to the rapid formation of coarse crystals, thus promoting the formation of a uniform and fine phosphating film. For example, citric acid was used in Example 1, while aminotrimethylenephosphonic acid (ATMP) was used in Example 2. The latter is a highly efficient organophosphonic acid complexing agent.
[0022] The oxidant is selected from at least one of sodium nitrate, sodium nitrite, sodium chlorate, hydrogen peroxide, and sodium perborate; It should be noted that the oxidant acts as an "accelerator" in the phosphating process. Its main function is to accelerate the uniform micro-corrosion of the metal substrate in the early stage of phosphating (activating the workpiece surface) and consume the hydrogen gas produced by the side reactions of the phosphating reaction, thereby reducing the porosity in the phosphating film and accelerating film formation.
[0023] The surfactant is a nonionic surfactant, selected from at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and sorbitan fatty acid ester polyoxyethylene ether. It should be noted that the main function of nonionic surfactants is to reduce the surface tension of the phosphating working solution, improve its wettability and penetration into the surface of metal workpieces (especially complex structures), and ensure that the phosphating solution can uniformly cover the surface, thereby obtaining a consistent phosphating film. In addition, it also helps to disperse solid particles in the system.
[0024] The pH buffer is selected from at least one of boric acid, borax, disodium hydrogen phosphate, and sodium bicarbonate; It should be noted that the phosphating reaction is very sensitive to the pH value of the solution. The role of the pH buffer is to stabilize the acidity or alkalinity of the phosphating working solution, keeping it within the optimal range (usually 2.5-3.5) during the process, and preventing the stability of the phosphating solution or the deterioration of the phosphating film quality due to excessive pH fluctuations.
[0025] A method for preparing a crystal form modifier for phosphating films includes the following steps: S1. In a reaction vessel, add 60%-80% of the formula amount of deionized water, heat to the first temperature, and add the main film-forming agent and the organic acid complexing agent in sequence while stirring. Continue stirring until completely dissolved to obtain clear solution A. It should be noted that heating (50-70℃) helps the main film-forming agent (phosphate) and the organic acid complexing agent dissolve more quickly and completely. Mixing the two in water beforehand allows the organic acid to immediately complex the metal ions dissociated from the main film-forming agent, forming a stable basic complex system, which prepares the system for the subsequent addition of other components.
[0026] S2. In another container, add the remaining deionized water, add the nanocrystal nucleus inducer while stirring, and process with a high-shear dispersion device to obtain a uniformly dispersed liquid B. It should be noted that nanomaterials are highly prone to agglomeration. This step aims to pre-disperse the nanocrystal nucleation inducing agents (such as nano-silica or alumina) into a stable suspension. Using a high-shear dispersion device (such as the high-shear dispersion emulsifier in Example 1, 10,000 rpm) is key to breaking up nanoparticle agglomerates and achieving their monodispersity or good dispersion, ensuring that they are uniformly distributed in the final product and effectively exert their heterogeneous nucleation effect.
[0027] S3. Cool the A solution obtained in step S1 to a second temperature, and add the rare earth complex, the oxidant, the surfactant and the pH buffer in sequence while stirring. Ensure that each component is completely dissolved before adding the next one. After all components are added and mixed evenly, slowly add the B solution obtained in step S2 while stirring. After adding all components, continue stirring for a third time, and then let it stand and mature for a fourth time to obtain the crystal form improver of the phosphating film. It's important to note that this step is the core mixing and stabilization process. Cooling solution A (to 30-45°C) first prevents certain components (such as some surfactants and oxidants) from decomposing or becoming ineffective at higher temperatures. "Adding sequentially and ensuring dissolution" prevents clumping or excessively high local concentrations caused by the simultaneous addition of multiple solid materials. "Slowly adding solution B" allows the nano-dispersion to smoothly integrate into the bulk solution, preventing re-aggregation of nanoparticles due to rapid mixing. Finally, "continuous stirring" and "stationary maturation" ensure the entire system reaches molecular / ionic homogeneity and dynamic equilibrium, guaranteeing product storage stability.
[0028] In step S1, the first temperature is 50℃-70℃; It should be noted that below 50℃, the main film-forming agent dissolves slowly and inefficiently; above 70℃, water may evaporate too quickly, increasing energy consumption. Within this temperature range, the components can be effectively dissolved without causing unnecessary side reactions.
[0029] In step S3, the second temperature is 30℃-45℃; It should be noted that excessively low temperatures (<30℃) may cause subsequent additions of solid components (such as certain rare earth complex salts and buffers) to dissolve slowly; excessively high temperatures (>45℃) may affect the stability of the added oxidants and surfactants. Cooling solution A to this range before mixing can balance dissolution efficiency and the stability of each component.
[0030] In step S3, the third time period is 30-60 minutes, and the fourth time period is 12-48 hours; It should be noted that the stirring time (30-60 minutes) ensures that the nanoparticles are further uniformly dispersed in the system after the addition of solution B, and that the components are fully miscible. The settling and maturation time (12-48 hours) is crucial. During this period, any tiny crystal nuclei or metastable particles that may exist in the system will dissolve or recombine, the solution will reach thermodynamic equilibrium, and the product performance will tend to stabilize. Insufficient maturation time may lead to uneven product performance or precipitation during storage.
[0031] Example 1 A crystal form improver for phosphating films comprises 30 parts zinc dihydrogen phosphate, 5 parts calcium dihydrogen phosphate, 8 parts cerium citrate complex (calculated as CeO2), 3 parts nano silica (average particle size 30nm), 5 parts citric acid, 5 parts sodium nitrate, 1.5 parts fatty alcohol polyoxyethylene ether (OP-10), 2 parts boric acid, and 150 parts deionized water.
[0032] Preparation method: S1. In a reaction vessel equipped with a stirrer and a heating mantle, add 120 parts of deionized water and heat to 60°C. Turn on the stirrer and add zinc dihydrogen phosphate, calcium dihydrogen phosphate and citric acid in sequence. Maintain the temperature at 60±2°C and stir for about 40 minutes until all solids are completely dissolved, to obtain a colorless or pale yellow clear solution A. S2. In another beaker, add the remaining 30 parts of deionized water and slowly add the nano silica powder while stirring at high speed (using a mechanical stirrer). After the addition is complete, transfer it to a high shear dispersion emulsifier and disperse it at 10,000 rpm for 15 minutes to obtain a translucent nano silica dispersion B. S3. Stop heating solution A and allow it to cool naturally to 40°C by circulating cooling water. While continuously stirring (at medium speed), add cerium citrate complex, sodium nitrate, OP-10, and boric acid to solution A sequentially. Stir for 5-10 minutes after each addition to ensure complete dissolution before adding the next. After all additions are complete, continue stirring for 10 minutes to homogenize the system. While maintaining stirring, slowly and gently add solution B to solution A through a funnel, a process that takes approximately 10 minutes. After adding solution B, reduce the stirring speed to medium-low and continue stirring for 50 minutes. Then stop stirring, seal the reactor, and allow it to mature at room temperature for 24 hours. After maturation, a slightly milky white, homogeneous, and stable liquid product is obtained, which is the phosphating film crystal form improver of this embodiment.
[0033] Example 2 A crystal form improver for phosphating films comprises 25 parts manganese dihydrogen phosphate, 10 parts zinc dihydrogen phosphate, 12 parts lanthanum gluconate complex (calculated as La2O3), 2 parts nano alumina (average particle size 50nm), 8 parts aminotrimethylene phosphonic acid (ATMP), 3 parts sodium chlorate, 1 part alkylphenol polyoxyethylene ether (Tx-10), 3 parts borax, and 180 parts deionized water.
[0034] Preparation method: S1. In a reaction vessel equipped with a stirrer and heating mantle, add 150 parts of deionized water and heat to 55°C. Turn on the stirrer and add manganese dihydrogen phosphate, zinc dihydrogen phosphate and gluconic acid in sequence. Maintain the temperature at 55±2°C and stir for about 40 minutes until all solids are completely dissolved, to obtain a colorless or pale yellow clear solution A. S2. In another beaker, add the remaining 30 parts of deionized water and slowly add the nano alumina powder while stirring at high speed (using a mechanical stirrer). After the addition is complete, transfer it to a high shear dispersion emulsifier and disperse it at 10,000 rpm for 15 minutes to obtain a translucent nano silica dispersion B. S3. Stop heating solution A and allow it to cool naturally to 35°C by circulating cooling water. While continuously stirring (at medium speed), add aminotrimethylene phosphonic acid, sodium chlorate, alkylphenol polyoxyethylene ether, and borax sequentially to solution A. Stir for 5-10 minutes after each addition to ensure complete dissolution before adding the next. After all additions are complete, continue stirring for 10 minutes to homogenize the system. While maintaining stirring, slowly and gently add solution B to solution A through a funnel, a process that takes approximately 10 minutes. After adding solution B, reduce the stirring speed to medium-low and continue stirring for 50 minutes. Then stop stirring, seal the reactor, and allow it to mature at room temperature for 36 hours. After maturation, a slightly milky white, homogeneous, and stable liquid product is obtained, which is the phosphating film crystal form improver of this embodiment.
[0035] In summary, the improvers prepared in the above embodiments are all designed to achieve the common technical effect of inducing the formation of a phosphating film with ultra-fine, dense, and uniform grains, dominated by stable phases such as zinc phosphate and calcium phosphate, through the synergistic effect of multiple mechanisms such as electrochemical catalysis and interfacial corrosion inhibition of rare earth complexes, heterogeneous nucleation of nanomaterials, and complexation and slow release of metal ions by organic acids. This solves the problems of coarse and uneven grains and insufficient corrosion resistance mentioned in the background art.
[0036] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0037] Although embodiments of the present invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the present invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A crystal form improver for phosphating films, comprising the following raw materials in parts by weight: 20-40 parts of main film-forming agent 5-15 parts of rare earth complex, 1-5 parts of nanocrystal nucleation inducer 3-10 parts of organic acid complexing agent 2-8 parts oxidant Surfactant 0.5-3 parts, 1-5 parts pH buffer 100-200 parts deionized water; The primary film-forming agent is at least one of zinc dihydrogen phosphate, manganese dihydrogen phosphate, and calcium dihydrogen phosphate; the rare earth complex is a water-soluble complex formed by a rare earth element and an organic ligand, wherein the rare earth element is selected from at least one of cerium, lanthanum, and yttrium; and the nanocrystal nucleation inducer is at least one of nano-silica, nano-alumina, and nano-zeolite powder, with an average particle size of 10-100 nanometers.
2. The crystal form improver for a phosphating film according to claim 1, characterized in that, The organic ligand in the rare earth complex is selected from at least one of citric acid, tartaric acid, gluconic acid, aminotrimethylphosphonic acid, and hydroxyethylidene diphosphonic acid.
3. The crystal form improver for a phosphating film according to claim 1, characterized in that, The organic acid complexing agent is selected from at least one of citric acid, tartaric acid, oxalic acid, aminotrimethylenephosphonic acid, and sodium ethylenediaminetetramethylenephosphonate.
4. The crystal form improver for a phosphating film according to claim 1, characterized in that, The oxidant is selected from at least one of sodium nitrate, sodium nitrite, sodium chlorate, hydrogen peroxide, and sodium perborate.
5. The crystal form improver for a phosphating film according to claim 1, characterized in that, The surfactant is a nonionic surfactant selected from at least one of fatty alcohol polyoxyethylene ether, alkylphenol polyoxyethylene ether, and sorbitan fatty acid ester polyoxyethylene ether.
6. The crystal form improver for a phosphating film according to claim 1, characterized in that, The pH buffer is selected from at least one of boric acid, borax, disodium hydrogen phosphate, and sodium bicarbonate.
7. A method for preparing a crystal form improver for a phosphating film as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. In a reaction vessel, add 60%-80% of the formula amount of deionized water, heat to the first temperature, and add the main film-forming agent and the organic acid complexing agent in sequence while stirring. Continue stirring until completely dissolved to obtain clear solution A. S2. In another container, add the remaining deionized water, add the nanocrystal nucleus inducer while stirring, and process with a high-shear dispersion device to obtain a uniformly dispersed liquid B. S3. Cool the A solution obtained in step S1 to a second temperature, and add the rare earth complex, the oxidant, the surfactant and the pH buffer in sequence while stirring. Ensure that each component is completely dissolved before adding the next one. After all components are added and mixed evenly, slowly add the B solution obtained in step S2 while stirring. After adding all components, continue stirring for a third time, and then let it stand and mature for a fourth time to obtain the crystal form improver of the phosphating film.
8. The method for preparing a crystal form improver for a phosphating film according to claim 7, characterized in that, In step S1, the first temperature is 50℃-70℃.
9. The method for preparing a crystal form improver for a phosphating film according to claim 7, characterized in that, In step S3, the second temperature is 30℃-45℃.
10. The method for preparing a crystal form improver for a phosphating film according to claim 7, characterized in that, In step S3, the third time period is 30-60 minutes, and the fourth time period is 12-48 hours.